PENGARUH KOMPETENSI STAF AKUNTANSI, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAN PENGELOLAAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada SKPD Kota Bukittinggi) - Putra Mhd Nazrin; M.Rasuli '; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted on employees SKPD Bukittinggi City. This research was included in the quantitative research. The type of data used in this research is the primary data by source. And then, in data collections sampling was conducted with a purposive sampling method (Sugiyono,2012: 392) with respondents as many as 87 employees who working in SKPD Bukittinggi City. Data were analyzed using multiple regression with SPSS version 20. This research aimed to know the influence of the Competency Of Accounting Staff, Application Of Financial Accounting System Of Local And Financial Management On The Quality Of Government Finance Report. The main problem that researcher descriptions are as follows: to see how many significant relationship between the dependent variable to the independent variable. The results of this research showed that Competency Of Accounting Staff have influence to the Quality Of Government Finance Report, Application Of Financial Accounting System have influence to the intention to carry out an Quality Of Government Finance Report, and Financial Management have influence to the intention to the Quality Of Government Finance Report. So that all the hypotheses presented in this research received.Keywords : Quality Of Government Finance Report, Competency Of Accounting Staff, Application Of Financial Accounting System, Financial Management.